Social Learning along International Migrant Networks - Yuan Tian; Maria Esther Caballero; Brian K. Kovak (Institute of Labor Economics (IZA), 2020)
We document the transmission of social distancing practices from the United States to Mexico along migrant networks during the early 2020 Covid-19 pandemic. Using data on pre-existing migrant connections between Mexican and U.S. locations and mobile-phone tracking data revealing social distancing behavior, we find larger declines in mobility in Mexican regions whose emigrants live in U.S. locations with stronger social distancing practices. We rule out confounding pre-trends and use a variety of controls and an instrumental variables strategy based on U.S. stay-at-home orders to rule out the potential influence of disease transmission and migrant sorting between similar locations. Given this evidence, we conclude that our findings represent the effect of information transmission between Mexican migrants living in the U.S. and residents of their home locations in Mexico. Our results demonstrate the importance of personal connections when policymakers seek to change fundamental social behaviors.
Keywords: J61; F22; I12; D83; 330; social learning; migration; Mexico-U.S.; network; COVID-19